Ongoing Crisis in Lack of Maternity Services in Rural America. Issue 2 (March 2020) - Simpson, Kathleen Rice
Abstract : Many women have limited access to basic maternity services in areas of the United States where there are no nurse midwives, nurse practitioners, family medicine physicians, or obstetricians, and no hospital with a maternity unit. Recommendations from the March of Dimes and Centers for Medicare and Medicaid Services for solving the crisis of maternity care deserts are reviewed.